2021
DOI: 10.1111/jcmm.16821
|View full text |Cite
|
Sign up to set email alerts
|

Pirfenidone modulates macrophage polarization and ameliorates radiation‐induced lung fibrosis by inhibiting the TGF‐β1/Smad3 pathway

Abstract: Radiation‐induced lung injury (RILI) mainly contributes to the complications of thoracic radiotherapy. RILI can be divided into radiation pneumonia (RP) and radiation‐induced lung fibrosis (RILF). Once RILF occurs, patients will eventually develop irreversible respiratory failure; thus, a new treatment strategy to prevent RILI is urgently needed. This study explored the therapeutic effect of pirfenidone (PFD), a Food and Drug Administration (FDA)‐approved drug for (IPF) treatment, and its mechanism in the trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 52 publications
3
32
0
Order By: Relevance
“…Accumulating evidence has shown that the M2 polarization of macrophages contributes to the development and progression of IPF through the secretion of cytokines [ 32 ] such as TGF-β1 and CTGF [ 5 , 33 , 34 ]. For instance, pirfenidone exerts its antifibrotic property in part by suppressing the TGF-β expression relevant to macrophage M2 polarization and fibroblast activation [ 35 ]. Furthermore, Neotuberostemonine (NTS), one of the traditional Chinese medicines included in all versions of the Chinese Pharmacopoeia, can effectively attenuate BLM-induced PF by suppressing the recruitment and polarization of M2 macrophages [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has shown that the M2 polarization of macrophages contributes to the development and progression of IPF through the secretion of cytokines [ 32 ] such as TGF-β1 and CTGF [ 5 , 33 , 34 ]. For instance, pirfenidone exerts its antifibrotic property in part by suppressing the TGF-β expression relevant to macrophage M2 polarization and fibroblast activation [ 35 ]. Furthermore, Neotuberostemonine (NTS), one of the traditional Chinese medicines included in all versions of the Chinese Pharmacopoeia, can effectively attenuate BLM-induced PF by suppressing the recruitment and polarization of M2 macrophages [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pirfenidone is one of the two targeted drugs approved by the US Food and Drug Administration for the treatment of IPF. Recently, Ying et al demonstrated that pirfenidone ameliorated fibrosis by attenuating M2 macrophage infiltration and inhibiting the activation of TGF‐ β 1/Smad3 pathway 27 . Guo et al demonstrated that neohesperidin inhibits TGF‐ β 1‐induced injury to alveolar epithelial cells and decreases TGF‐ β 1‐induced myofibroblast differentiation, extracellular matrix production and fibroblast migration.…”
Section: Discussionmentioning
confidence: 99%
“…Pirfenidone was found to inhibit the TGF-β-induced phosphorylation of Smad3, p38, and Akt, key factors in the TGF-β pathway 36 and to regulate macrophage polarization and reduce radiation-induced pulmonary fibrosis by inhibiting the TGF-β1/Smad3 pathway. 37 LY2109761 is a novel selective TGF-β inhibitor that inhibits on the phosphorylation of Smad2, attenuating radiation-induced pulmonary fibrosis in mice by inhibiting the TGF-β1/Smad2 pathway. 38 These results suggest that inhibiting TGF-β1 attenuates lung injury.…”
Section: Discussionmentioning
confidence: 99%